Determination of isoniazid content via cysteic acid/graphene modified glassy carbon electrode. Issue 2 (10th December 2014) - Si, Xiaojing; Jiang, Lin; Wang, Xinyue; Ding, Yaping; Luo, Liqiang
Abstract : The electrodeposited graphene (EGR) and cysteic acid (CA) composite (CA/EGR) was fabricated through an electrochemical method for the modification of glassy carbon electrode (GCE). The obtained detection linearity of isoniazid at the CA/EGR/GCE ranged from 0.1 to 200 μM with the detection limit of 0.03 μM ( S / N = 3). Abstract : The electrodeposited graphene (EGR) and cysteic acid (CA) composite (CA/EGR) was fabricated through an electrochemical method for the modification of glassy carbon electrode (GCE). Fourier transform infrared spectroscopy (FT-IR) was carried out to characterize the proposed CA film. The electrochemical performance of the CA/EGR modified GCE (CA/EGR/GCE) was demonstrated with cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The modified GCE was designed to act as an electrochemical sensor for isoniazid. The obtained detection linearity at the CA/EGR/GCE ranged from 0.1 to 200 μM with the detection limit of 0.03 μM ( S / N = 3). Moreover, the sensor was employed for practical sample analysis with satisfactory recoveries, further validating the reliable practicability for electroanalysis. In addition, CA/EGR/GCE also displayed good reproducibility, high stability and excellent anti-interference ability for the determination of isoniazid.